2021
DOI: 10.4236/nr.2021.121001
|View full text |Cite
|
Sign up to set email alerts
|

Determine the Optimal Density of Nile Tilapia (<i>Oreochromis niloticus</i>) Fingerlings Cultured in Floating Cages

Abstract: The objective of the study was to determine the optimal density of fingerlings of the Nile tilapia (Oreochromis niloticus) culture in floating cages with respect to growth performance and to know the effect of temperature on growth during the winter period. Tilapia fingerlings (mean weight 8.5 ± 0.36 g) were stocked at densities of 120, 180 and 360 fish/m 3 for 10 weeks. During culture, fish were fed a diet contains 35% protein made of peanut seed, cottonseed, wheat bran, and Sorghum. The results showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Our findings were similar to the findings of Gibtan et al (2008), who reported a positive relationship between the stocking density and the Nile tilapia production. The higher yields as stocking densities increased were also found by El Nouman et al (2021).…”
Section: Productionmentioning
confidence: 60%
“…Our findings were similar to the findings of Gibtan et al (2008), who reported a positive relationship between the stocking density and the Nile tilapia production. The higher yields as stocking densities increased were also found by El Nouman et al (2021).…”
Section: Productionmentioning
confidence: 60%
“…Overstocking is a major stressor in tilapia culture and can lead to an increase in competition and aggression in the population. El Nouman et al 128 reported that tilapia fingerlings reared in floating cages had the best performance at a medium density of 240 fish‐m 3 . Excessive handling, which can occur during transportation, vaccination or treatments, is also very stressful for fish 129 …”
Section: Implementing Biosecurity Measures In the Value Chainmentioning
confidence: 99%
“…Produktivitas untuk setiap petak KJA SMART lebih besar jika dibandingkan dengan KJA jaring ganda di Danau Maninjau dimana panen ikan mas dan nila yang diperoleh masing-masing sebesar 5,3 dan 2,3 kali dari biomassa ikan tebaran (Triyanto et al, 2005). Selain oleh kandungan protein dalam pakan, laju pertumbuhan ikan juga dipengaruhi oleh kepadatan ikan pada saat pemeliharaan (Nouman et al, 2021). Kepadatan ikan yang tinggi akan berdampak pada nilai FCR yang tinggi dan kelangsungan hidup ikan yang rendah (Khairnar et al, 2020).…”
Section: Pembahasanunclassified